An extensive immunohistochemical analysis of 290 ovarian adult granulosa cell tumors with 29 markers - Němejcová, Kristýna; Šafanda, Adam; Kendall Bártů, Michaela; Michálková, Romana; Švajdler, Marián; Shatokhina, Tetiana; Laco, Jan; Matěj, Radoslav; Méhes, Gábor; Drozenová, Jana; Hausnerová, Jitka; Špůrková, Zuzana; et al. (Virchows Archiv, 2024)
The current knowledge about the immunohistochemical features of adult granulosa cell tumor (AGCT) is mostly limited to the "traditional" immunohistochemical markers of sex cord differentiation, such as inhibin, calretinin, FOXL2, SF1, and CD99. Knowledge about the immunohistochemical markers possibly used for predictive purpose is limited. In our study, we focused on the immunohistochemical examination of 290 cases of AGCT classified based on strict diagnostic criteria, including molecular testing. The antibodies used included 12 of the "diagnostic" antibodies already examined in previous studies, 10 antibodies whose expression has not yet been examined in AGCT, and 7 antibodies with possible predictive significance, including the expression of HER2, PD-L1, CTLA4, and 4 mismatch repair (MMR) proteins. The results of our study showed expression of FOXL2, SF1, CD99, inhibin A, calretinin, ER, PR, AR, CKAE1/3, and CAIX in 98%, 100%, 90%, 78%, 45%, 41%, 94%, 82%, 26%, and 9% of AGCT, respectively. GATA3, SATB2, napsin A, MUC4, TTF1, and CD44 were all negative. PTEN showed a loss of expression in 71% of cases and DPC4 in 4% of cases. The aberrant staining pattern (overexpression) of p53 was found in 1% (3/268) of cases, 2 primary tumors, and 1 recurrent case. Concerning the predictive markers, the results of our study showed that AGCT is microsatellite stable, do not express PD-L1, and are HER2 negative. The CTLA4 expression was found in almost 70% of AGCT tumor cells.
Keywords: Ovarian tumors; imunohistochemie; Middle Aged; nádory vaječníků; Adult; Sex cord-stromal tumors; Biomarkers, Tumor; Immunohistochemistry; ženské pohlaví; nádorové biomarkery; Humans; Granulosa Cell Tumor; lidé středního věku; Granulosa cell tumors; nádor z folikulárních buněk; dospělí; Female; Ovarian Neoplasms; lidé